Secrets of Endometrial Receptivity: Some Are Hidden in Uterine Secretome. (March 2016) - Bhusane, Kashmira; Bhutada, Sumit; Chaudhari, Uddhav; Savardekar, Lalita; Katkam, Rajendra; Sachdeva, Geetanjali
Abstract : Problem: Endometrium, the innermost mucosal layer of the uterus, serves as a lodge for the embryo in eutherian mammals. The endometrium is constituted of various cell types, and each cell type executes specific functions to facilitate embryo implantation and development. It is well established that the endometrium, despite being non‐permissive to the embryo for the major period of a menstrual cycle, is irreplaceable in the scheme of events essential for procreation. However, the embryo, before initiating physical contact with the endometrium, encounters the uterine cavity that remains bathed in uterine fluid. Uterine fluid is an admixture of endometrial secretions, plasma transudates, and oviductal fluid. Uterine fluid components are believed to play important roles in immunosuppression and embryo development during peri‐implantation period. Uterine fluid is also involved in defense against pathogens, sperm migration, and lubrication of endometrium. The advent of high‐throughput functional genomics tools has created enormous opportunities to investigate the uterine fluid for its protein repertoire and modulation during the receptive phase of an endometrial cycle in animals and humans. Towards this, few investigations have been conducted in recent years. The data obtained using non‐targetted functional genomics approaches need to be assimilated with the existing information on specific components of uterine fluid. Method: This review compiles existing information on the composition of uterine fluid and its significance in endometrial functions and dysfunctions. Result: Collectively, investigations based on targetted and non‐targetted approaches have revealed the presence of several cytokines, growth factors, ions, carbohydrates, and steroids, in human uterine fluid. Conclusion: Detailed investigations of human uterine fluid, especially directed towards the elucidation of functional relevance of different proteins in uterine fluid, will help identify novel markers of endometrial receptivity and also gain significant insights into the mechanisms underlying unexplained infertility, recurrent pregnancy losses, and other endometrial pathologies.